2020
DOI: 10.1007/s10456-020-09745-7
|View full text |Cite
|
Sign up to set email alerts
|

A drug-tunable Flt23k gene therapy for controlled intervention in retinal neovascularization

Abstract: Gene therapies that chronically suppress vascular endothelial growth factor (VEGF) represent a new approach for managing retinal vascular leakage and neovascularization. However, constitutive suppression of VEGF in the eye may have deleterious side effects. Here, we developed a novel strategy to introduce Flt23k, an intraceptor that binds intracellular VEGF, fused to the destabilizing domain (DD) of Escherichia coli dihydrofolate reductase (DHFR) into the retina. The expressed DHFR(DD)-Flt23k fusion protein is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…When the myocardial cell membrane is damaged, LDH is rapidly released from the cells in the culture medium. Therefore, LDH can be used as an indicator of cell damage caused by H/R [ 58 , 59 ]. Our data showed that LATS2 suppression significantly reduced the LDH content in the medium and this effect was dependent on the PGC1 α -associated mitochondrial biogenesis [ 60 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the myocardial cell membrane is damaged, LDH is rapidly released from the cells in the culture medium. Therefore, LDH can be used as an indicator of cell damage caused by H/R [ 58 , 59 ]. Our data showed that LATS2 suppression significantly reduced the LDH content in the medium and this effect was dependent on the PGC1 α -associated mitochondrial biogenesis [ 60 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…LPS-associated myocardial damage could be attenuated by MKP-1 through reducing inflammatory response [63]. Oxidative stress-mediated endothelial cell injury was associated with ER stress due to a loss of MKP-1 activity [64,65]. Overexpression of MKP-1 reduced ER stress, resulting in increased neural cell survival [66].…”
Section: Discussionmentioning
confidence: 99%
“…After 30 min, PI was removed, and the cells were washed twice with the medium [ 33 ]. The number of PI-positive cells was determined using fluorescence microscopy with an excitation of 535 nm and emission of 617 nm at 200x magnification [ 34 ].…”
Section: Methodsmentioning
confidence: 99%